2018
DOI: 10.1016/j.nano.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid conjugated nanoparticle delivery of siRNA against TWIST reduces tumor burden and enhances sensitivity to cisplatin in ovarian cancer

Abstract: TWIST protein is critical to development and is activated in many cancers. TWIST regulates epithelial-mesenchymal transition, and is linked to angiogenesis, metastasis, cancer stem cell phenotype, and drug resistance. The majority of epithelial ovarian cancer (EOC) patients with metastatic disease respond well to first-line chemotherapy but most relapse with disease that is both metastatic and drug resistant, leading to a five-year survival rate under 20%. We are investigating the role of TWIST in mediating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 56 publications
1
50
0
Order By: Relevance
“…In another study, a TWIST1-specific siRNA was delivered in ovarian and breast cancer cells by polyamidoamine dendrimers (PAMAM) and hyaluronic acid conjugated mesoporous silica nanoparticles (MSN-HAs). These nanoformulations inhibited the EMT program, reversing chemoresistance to cisplatin and leading a reduction of tumor growth in mice models [83,84,87].…”
Section: Twist1mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, a TWIST1-specific siRNA was delivered in ovarian and breast cancer cells by polyamidoamine dendrimers (PAMAM) and hyaluronic acid conjugated mesoporous silica nanoparticles (MSN-HAs). These nanoformulations inhibited the EMT program, reversing chemoresistance to cisplatin and leading a reduction of tumor growth in mice models [83,84,87].…”
Section: Twist1mentioning
confidence: 99%
“…A plethora of studies reported that siRNAs against TWIST1 delivered by nanoparticles inhibited the EMT process in several tumors, leading to the reduction of tumor progression and metastasis and sensitizing cancer cells to chemotherapy drugs and radiotherapy [83][84][85][86][87]111,112,181,182].…”
Section: Twist1mentioning
confidence: 99%
“…In addition, HA has been also used for its targeting ability. In an example by Glackin, MSNs were modified to A c c e p t e d M a n u s c r i p t accomplish codelivery of cisplatin and siRNA [82]. In this system, the gatekeeper role was assigned to a polyethyleneimine mesh onto which the siRNA was adsorbed.…”
Section: Saccharidesmentioning
confidence: 99%
“…Hypoxia exposure leads to an increase in TWIST expression. Hyaluronic-acid conjugated mesoporous silica nanoparticles (MSN-HAs) loaded with TWIST siRNA successfully suppressed TWIST expression in vitro, subsequently reducing the tumour burden in a model of epithelial ovarian cancer in vivo [33]. Furthermore, amphiphilic polymer-based nanoparticles loaded with siRNAs against SNAIL and TWIST, and used in combination with the chemotherapeutic paclitaxel, inhibited tumour growth and metastasis of the 4T1 breast cancer model in vivo, while siRNA alone exhibited only modest benefits (Figure 1) [32].…”
Section: Targeting Emt and Metastatic Progression With Nanoparticle Fmentioning
confidence: 99%